Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/php.13146
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Photochemical Internalization to Heat, pH and Ca2+ Ions

Abstract: The inefficient endosomal escape of drugs or macromolecules is a major obstacle to achieving successful delivery to therapeutic targets. An efficient approach to circumvent this barrier is photochemical internalization (PCI), which uses light and photosensitizers for endosomal escape of the delivered macromolecules. The PCI mechanism is related to photogenerated singlet oxygen, but the mechanism is still unclear. In this study, we examined the relation of PCI to heat, pH and Ca2+ ions using cell penetrating pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…Photoinduced endosomal escape has been recently reported as an attractive avenue for membrane disruption. In this approach, reactive oxygen species (ROS) and singlet oxygen ( 1 O 2 ) are generated from photosensitizers [ 305 , 306 ] or photothermal transduction agents [ 305 , 307 , 308 ] to induce membrane destabilization. These endosomal escape strategies have been termed photochemical internalization (PCI) [ 306 ] and photothermal therapy (PTT), respectively [ 309 ].…”
Section: Enhancing Ion Endosomal Escapementioning
confidence: 99%
See 1 more Smart Citation
“…Photoinduced endosomal escape has been recently reported as an attractive avenue for membrane disruption. In this approach, reactive oxygen species (ROS) and singlet oxygen ( 1 O 2 ) are generated from photosensitizers [ 305 , 306 ] or photothermal transduction agents [ 305 , 307 , 308 ] to induce membrane destabilization. These endosomal escape strategies have been termed photochemical internalization (PCI) [ 306 ] and photothermal therapy (PTT), respectively [ 309 ].…”
Section: Enhancing Ion Endosomal Escapementioning
confidence: 99%
“…This damage promotes endocytic vesicle disruption, which ultimately results in endosomal escape ( Figure 8 B). Several researchers have reported that the success of PCI depends on the capability of PSs to enter cells through pinocytic pathways and subsequently localize in endocytic membranes [ 305 , 310 , 312 , 315 ]. The most efficient PSs for PCI have an amphiphilic structure, which allows them to intercalate within endocytic membranes [ 306 , 312 , 314 ].…”
Section: Enhancing Ion Endosomal Escapementioning
confidence: 99%
“…Cathepsins have also been reported elsewhere, to cleave the apoptosis inhibitor Bcl2, further promoting the apoptotic processes [102]. Lysosomal rupture by PDT has been shown to induce accumulation of Ca 2+ in the cytosol, most likely released from the lysosomes, with the involvement, however, of extracellular Ca 2+ not being excluded [87]. The increased accumulation of Ca 2+ in the cytosol usually results in rapid sequestration of excess Ca 2+ by mitochondria and post-PDT inhibition of this sequestration has been shown to reduce cell death, likely due to the inhibition of Ca 2+ -induced opening of the pro-apoptotic mitochondrial permeability transition pore [103].…”
Section: Treatment Effects On Endocytic Vesiclesmentioning
confidence: 87%
“…The inhibitory effect of bafilomycin a1 on the AlPcS 2a -based PCI-induced transfection efficacy was tentatively attributed to the inhibitory effects of bafilomycin a1 on endocytosis, but this has not been unequivocally confirmed. In the reports by Wang et al [87] and Dondi et al [88] CPP and other cationic peptides were linked to a highly hydrophobic PS that may incorporate deeper into the endolysosomal membranes and thus result in an enhanced uptake as compared to TPPS 2a and a strong PCI activation of the protein-toxin saporin. It has been reported that the arginine in the CPP TAT-peptide (linked to a rhodamine derivative used as PS) contributes to the destabilization of photosensitized membranes [89].…”
Section: Treatment Effects On Endocytic Vesiclesmentioning
confidence: 99%
“…For example, PCI mediated by TAMRA-attached Tat peptide (TMR-Tat) leads to disruption of calcium homeostasis [63]. PCI-associated changes in intracellular calcium levels were also observed using TatU1A-Alexa546 after irradiation [64]. In addition, a low pH in the endosome is required for the photoinduced endosomal escape of TatU1A-Alexa546 [64].…”
Section: Mechanism Of Pci Using Cpp-ps Conjugatesmentioning
confidence: 99%